2014
DOI: 10.1002/arch.21190
|View full text |Cite
|
Sign up to set email alerts
|

DIVERSITY IN GUT MICROFLORA OF Helicoverpa armigera POPULATIONS FROM DIFFERENT REGIONS IN RELATION TO BIOLOGICAL ACTIVITY OF Bacillus thuringiensis δ‐ENDOTOXIN Cry1Ac

Abstract: Transgenic crops expressing toxin proteins from Bacillus thuringiensis (Bt) have been deployed on a large scale for management of Helicoverpa armigera. Resistance to Bt toxins has been documented in several papers, and therefore, we examined the role of midgut microflora of H. armigera in its susceptibility to Bt toxins. The susceptibility of H. armigera to Bt toxin Cry1Ac was assessed using Log-dose-Probit analysis, and the microbial communities were identified by 16S rRNA sequencing. The H. armigera populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Survival of H. armigera larvae fed on diets with Bt proteins was directly proportional to the concentration of antibiotics in the artificial diet [11,36]. It was observed that the larvae gain weight when fed on diet containing antibiotic cocktail, and similar trend observed in L. dispar [10] and M. sexta raised on antibiotics attained more weight than insects reared on regular diet [37]. The increase in larval weight was probably due to elimination of microbes resulting in nutrient deficit, so that food intake was more to fulfill the nutrient loss.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Survival of H. armigera larvae fed on diets with Bt proteins was directly proportional to the concentration of antibiotics in the artificial diet [11,36]. It was observed that the larvae gain weight when fed on diet containing antibiotic cocktail, and similar trend observed in L. dispar [10] and M. sexta raised on antibiotics attained more weight than insects reared on regular diet [37]. The increase in larval weight was probably due to elimination of microbes resulting in nutrient deficit, so that food intake was more to fulfill the nutrient loss.…”
Section: Discussionmentioning
confidence: 53%
“…Protease-producing midgut bacterial species belong to Bacillus sp., and the studies on their role in potentiation and/or detoxification of Bt toxins are under progress. Composition of gut microbes varies across crop host plants and locations [10]; however, there are some bacterial strains which are common in most of the populations of H. armigera. Information on bacterial strains involved in potentiation and/or detoxification of the Bt toxins will be useful globally to develop strategies to delay the development of resistance in the insect pests to Bt transgenic crops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have already shown that a higher tolerance to Bt is associated with a difference in bacterial community composition [ 32 , 33 ]. Nevertheless, whether changes in microbiota content are the cause of an increased tolerance or a consequence of Bt infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes have been documented to influence the susceptibility of lepidopteran insects targeted by Bt plants. Gut microbiota actually appear to be required for Bt susceptibility in lepidopteran pests [85][86][87][88][89]. Gut microbes also play a role in crop rotation resistance in D. v. virgifera, but the role of gut microbiota in Bt resistance and susceptibility is unknown [37].…”
Section: Microbes and Their Implications For Bt Resistancementioning
confidence: 99%